Polishing-free preparation process and application of double-layer metal composite ultra-thin strip
Through the grinding-free preparation process, the preparation process of the double-layer metal composite extremely thin strip is simplified, the production efficiency is improved, and the material performance is improved, solving the problems of complex processes and high costs in the existing technology.
Patent Information
- Application Number
- CN202411764207.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The preparation process of the double-layer metal composite extremely thin strip is complicated and requires fine grinding and pretreatment of the material surface, resulting in high production costs and complex process flow.
The double-layer metal composite extremely thin strip is prepared by using the grinding-free preparation process, through precise tailing, pre-rolling annealing, cleaning, co-rolling of lacquer rolls and traditional flat rolls, and post-rolling annealing, forming a regularly distributed pit array structure.
The production process flow is simplified, the production efficiency is improved, the bonding strength of the composite interface is improved, and the materials are given good hydrophobicity, reduce heat transfer, reduce air resistance, reduce electromagnetic wave reflection and scattering.
Smart Images

Figure CN119525273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of double-layer metal composite ultra-thin strips, and in particular to a grinding-free preparation process and application of a double-layer metal composite ultra-thin strip. Background Art
[0002] Double-layer metal composite ultra-thin strip is a new type of composite material formed by composite technology of at least two alloys or metals with different physical properties, chemical attributes and mechanical properties. Through careful design and combination, this type of composite material can fully utilize and give full play to the performance advantages of each component material, effectively make up for the limitations of a single material, and thus give the final product excellent comprehensive performance. For this reason, double-layer metal composite ultra-thin strip has shown wide application potential and value in many high-tech and industrial fields such as aerospace, electronic communications, and petrochemicals.
[0003] At present, the composite technology of double-layer metal composite ultra-thin strips mainly covers several methods such as solid-solid phase composite, solid-liquid phase composite and liquid-liquid phase composite. Among them, the rolling process in the field of solid-solid phase composite has become the mainstream production method of double-layer metal composite ultra-thin strips widely adopted by the industry due to its significant advantages of low energy consumption and high efficiency. Specifically, the rolling composite process of double-layer metal composite ultra-thin strips can be divided into two categories: the first category is to pre-roll the raw materials first, and then roll composite; the second category is to directly roll composite the raw materials first, and then further roll the composite materials. Both of the above processes require fine grinding pretreatment of the composite interface before rolling composite, aiming to expose the fresh metal surface and ensure the smooth progress of the rolling composite process. Therefore, the final effect of rolling composite is closely related to the grinding process of the material surface and its surface state after treatment, which makes the entire preparation process of double-layer metal composite ultra-thin strips complicated and cumbersome, and the production cost is relatively high. Summary of the invention
[0004] In view of this, the present invention provides a grinding-free preparation process and application of a double-layer metal composite ultra-thin strip. The grinding-free preparation process of the present invention does not require grinding treatment on the surface of the material, which greatly simplifies the production process and improves production efficiency. At the same time, the interface of the composite material prepared by the present invention presents a regularly distributed pit array structure, which not only improves the bonding strength of the composite interface, but also gives the material good hydrophobicity, reduces heat transfer, reduces air resistance, reduces reflection and scattering of electromagnetic waves, etc., so that it has unique advantages in high-end fields such as aerospace and electronics industries, and has good application prospects.
[0005] The grinding-free preparation process of the double-layer metal composite ultra-thin strip of the present invention comprises the following steps:
[0006] S1. Precisely cutting the metal thin strip to obtain the metal substrate;
[0007] S2, annealing the metal substrate before rolling;
[0008] S3, cleaning the metal substrate after annealing before rolling;
[0009] S4, stacking the cleaned metal substrates and rolling them together with a textured roller and a conventional flat roller;
[0010] S5. After rolling is completed, post-rolling annealing and cooling are performed to obtain a double-layer metal composite ultra-thin strip.
[0011] Preferably, the metal ultra-thin strip is any two of copper foil, titanium foil and alloy strip. More preferably, the alloy strip is a stainless steel strip.
[0012] Preferably, the pre-rolling annealing temperature is 500°C to 950°C, and the holding time is 5 to 10 minutes.
[0013] Preferably, the texturing roller is laminated to a metal substrate with high hardness, and the conventional flat roller is laminated to a metal substrate with low hardness.
[0014] Preferably, the rolling force of the rolling is 7-12 kN, and the rolling speed is 0.1 m / min.
[0015] Preferably, the post-rolling annealing temperature is preferably 650° C. to 850° C., and the holding time is 3 to 10 minutes.
[0016] The present invention also provides an application of a double-layer metal composite ultra-thin strip in the aerospace and electronics industries. The double-layer metal composite ultra-thin strip is the double-layer metal composite ultra-thin strip described in the above technical solution.
[0017] Compared with the prior art, the preparation process of the present invention only requires the oil removal operation on the surface of the rolled piece, and abandons the cumbersome grinding treatment steps for the surface of the material to be composited. It not only greatly simplifies the production process, but also fundamentally improves the overall production efficiency of the double-layer metal composite ultra-thin strip. In addition, the present invention realizes the rolling composite of a variety of different metal thin strip substrates at a relatively low reduction rate, breaking the strict restrictions of traditional processes on materials and reduction rates, and opening up a broader application space for the preparation of ultra-thin strip composite materials. Finally, the interface of the composite material prepared by the present invention presents a regularly distributed pit array structure. This unique structure not only significantly improves the bonding strength of the composite interface, but also gives the material good hydrophobicity, reduces heat transfer, reduces air resistance, reduces the reflection and scattering of electromagnetic waves, etc., which makes it have unique advantages in high-end fields such as aerospace and electronics industries, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention will be further described below in conjunction with the accompanying drawings.
[0019] Figure 1 This is a three-dimensional profile image of the double-layer metal composite ultra-thin strip of Example 1, where a and b are protrusions on the copper foil side, and c and d are depressions on the 304 stainless steel side;
[0020] Figure 2 This is a SEM image of the rolled product surface where the double-layer metal composite ultra-thin strip is attached to the texturing roller side in Example 1;
[0021] Figure 3 The textured roller (bottom) and the conventional flat roller (top) used in the present invention;
[0022] Figure 4 A three-dimensional contour morphology diagram of the surface of the texturing roller used in the present invention;
[0023] Figure 5 It is a schematic diagram of the rolling process;
[0024] Figure 6 It is a schematic diagram of the surface structure of the roughened roller;
[0025] Explanation of the accompanying drawings: 1. Traditional flat roller; 2. Metal substrate with low hardness; 3. Metal substrate with high hardness; 4. Roughened roller. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention provides a grinding-free preparation process for a double-layer metal composite ultra-thin strip, comprising the following steps:
[0028] S1. Precisely cutting the metal thin strip to obtain the metal substrate;
[0029] S2, annealing the metal substrate before rolling;
[0030] S3, cleaning the metal substrate after annealing before rolling;
[0031] S4, stacking the cleaned metal substrates and rolling them together with a textured roller and a conventional flat roller;
[0032] S5. After rolling is completed, post-rolling annealing and cooling are performed to obtain a double-layer metal composite ultra-thin strip.
[0033] The first step of the present invention is to accurately cut the metal ultra-thin strip to obtain the metal substrate, specifically: select the metal material as the composite metal substrate, and ensure that the size of each substrate meets the preset standard through precise cutting, so as to provide a good foundation for the subsequent composite process.
[0034] In some specific embodiments of the present invention, the metal ultra-thin strip is preferably any two of copper foil, titanium foil, and alloy strip. In some other specific embodiments of the present invention, the alloy strip is preferably a stainless steel strip. In some preferred embodiments of the present invention, the stainless steel strip is preferably a 304 stainless steel strip. The metal substrate in the present invention is not limited to a single material, but innovatively adopts a combination of dissimilar materials. At the same time, when it comes to the composite of two ultra-thin strips, the grinding-free preparation process of the present invention does not need to be limited to the thickness of the metal substrate. Because the present invention can select roughened rollers with different roughness according to metal substrates of different thicknesses to ensure that the two metal substrates can form a good interface bonding during the rolling process, thereby realizing the preparation of double-layer metal composite ultra-thin strips.
[0035] The second step of the present invention is to perform pre-rolling annealing on the cut metal substrate, and the pre-rolling annealing is performed in an inert gas atmosphere, and the pre-rolling annealing temperature is preferably 500°C to 950°C, and the holding time is preferably 5 to 10 minutes. In some preferred embodiments of the present invention, the inert gas is argon; when the metal substrate is stainless steel, the pre-rolling annealing temperature is preferably 950°C, and the holding time is preferably 5 minutes; when the metal substrate is copper foil, the pre-rolling annealing temperature is preferably 500°C, and the holding time is preferably 10 minutes; when the metal substrate is titanium foil, the pre-rolling annealing temperature is preferably 600°C, and the holding time is preferably 10 minutes.
[0036] The present invention ensures that the microstructure inside the material is optimized by annealing before rolling, and prevents the material from being oxidized during the annealing process by controlling the atmosphere.
[0037] The third step of the present invention is to clean the metal substrate after annealing before rolling. In some specific embodiments of the present invention, the cleaning is performed using anhydrous ethanol and / or dust-free paper. The present invention effectively removes impurities, oil stains and other pollutants on the surface of the material by cleaning the metal substrate after annealing before rolling, so as to facilitate subsequent rolling.
[0038] The fourth step of the present invention is to stack the cleaned metal substrates and then roll them together with a roughened roller and a conventional flat roller. In some specific embodiments of the present invention, the roughened roller is bonded to a metal substrate with high hardness, and the conventional flat roller is bonded to a metal substrate with low hardness. The two substrates are then sent to a flat roller mill for rolling and compounding. The roughness of the roughened roller is preferably 5 to 50 μm. In some specific embodiments of the present invention, the rolling force of the rolling is 7 to 12 kN, and the rolling speed is 0.1 m / min. However, the present invention does not strictly limit the roughness of the roughened roller, and different specifications of roughened rollers can be customized according to specific needs for rolling, ultimately ensuring the uniformity and consistency of the surface pit array structure of the double-layer metal composite ultra-thin strip. Generally speaking, the thicker the thin strip, the greater the corresponding roughness of the roughened roller should be, so as to form an ideal pit array structure.
[0039] The fifth step of the present invention is to perform post-rolling annealing. In some specific embodiments of the present invention, the post-rolling annealing temperature is preferably 650° C. to 850° C., and the holding time is preferably 3 to 10 minutes.
[0040] The metal composite material obtained in step 4 is subjected to a post-rolling annealing treatment, wherein the post-rolling annealing is performed in an inert gas atmosphere. In some preferred embodiments of the present invention, the inert gas is argon.
[0041] The invention prevents oxidation of the material during the annealing process by controlling the post-rolling annealing atmosphere.
[0042] The present invention also provides an application of a double-layer metal composite ultra-thin strip in the fields of aerospace, electronics industry, and petrochemical industry. The double-layer metal composite ultra-thin strip is the double-layer metal composite ultra-thin strip described in the above technical solution.
[0043] The double-layer metal composite ultra-thin tape of the present invention has a pit array structure and can be used as a coating material on the surface of an aircraft (such as an airplane, a rocket, a satellite, etc.). The regular pit array structure of the double-layer metal composite ultra-thin tape of the present invention can reduce air resistance and improve flight efficiency. At the same time, the pit array structure can improve the hydrophobicity of the material, help prevent the fuselage from icing, and ensure flight safety. In the thermal protection system of an aerospace vehicle, the double-layer metal composite ultra-thin tape of the present invention can be used as a component of a thermal insulation layer or a heat-resistant tile, and its regular structure and hydrophobicity help reduce heat transfer and protect the internal structure from high temperature damage. In addition, the double-layer metal composite ultra-thin tape of the present invention can be used as a coating material on the surface of a car body to reduce air resistance during driving and improve fuel efficiency. At the same time, its hydrophobicity helps prevent water accumulation in the car body and reduces corrosion and wear. In radar and communication systems, the double-layer metal composite ultra-thin tape of the present invention can be used as a material for a radome, and the regular pit array structure helps reduce the reflection and scattering of electromagnetic waves and improve the transmission quality of signals.
[0044] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples of the present invention are all commercially available.
[0045] Unless otherwise specified, all experiments were repeated 3 times and the results were expressed as mean values.
[0046] Example 1 A grinding-free preparation process for a copper / 304 stainless steel composite ultra-thin strip, the steps are as follows:
[0047] S1. Precisely cut a copper foil with a thickness of 20 μm and a 304 stainless steel ultra-thin strip with a thickness of 20 μm as a composite metal substrate, and the specifications of the substrate are 130 mm×15 mm;
[0048] S2. Place the cut copper foil and 304 stainless steel ultra-thin strip into an annealing furnace respectively, and perform pre-rolling annealing treatment under argon protection, wherein the pre-rolling annealing treatment temperature of 304 stainless steel is 950°C, the holding time is 5 minutes, and the pre-rolling annealing treatment temperature of copper foil is 500°C, the holding time is 10 minutes. After the annealing is completed, the material is cooled to room temperature with the furnace;
[0049] S3. Use dust-free paper to gently wipe the surface of the copper foil and 304 stainless steel ultra-thin strip to be laminated to remove possible oil stains and impurities;
[0050] S4, closely laminating the treated 304 stainless steel ultra-thin strip with a roughened roller with a roughness of 15 μm, laminating the copper foil with a smooth flat roller, stacking the two materials, and rolling and laminating them at a rolling force of 12 kN and a rolling speed of 0.1 m / min to obtain a composite ultra-thin strip;
[0051] S5. Put the composite ultra-thin strip into an annealing furnace and perform post-rolling annealing treatment under argon protection. The post-rolling annealing treatment temperature is 850° C. and the holding time is 3 min. After the heat treatment is completed, the material is cooled to room temperature with the furnace to obtain a copper / 304 stainless steel composite ultra-thin strip.
[0052] Replacing the textured roll with a smooth flat roll does not achieve lamination.
[0053] Example 2 A grinding-free preparation process for a copper / 304 stainless steel composite ultra-thin strip, the steps are as follows:
[0054] S1. Precisely cut a copper foil with a thickness of 20 μm and a 304 stainless steel ultra-thin strip with a thickness of 10 μm as a composite metal substrate, and the specifications of the substrate are 130 mm×15 mm;
[0055] S2. Place the cut copper foil and 304 stainless steel ultra-thin strip into an annealing furnace respectively, and perform pre-rolling annealing treatment under argon protection, wherein the pre-rolling annealing treatment temperature of 304 stainless steel is 950°C, the holding time is 5 minutes, and the pre-rolling annealing treatment temperature of copper foil is 500°C, the holding time is 10 minutes. After the annealing is completed, the material is cooled to room temperature with the furnace;
[0056] S3. Use dust-free paper to gently wipe the surface of the copper foil and 304 stainless steel ultra-thin strip to be laminated to remove possible oil stains and impurities;
[0057] S4, closely laminating the treated 304 stainless steel ultra-thin strip with a roughened roller with a roughness of 10 μm, laminating the copper foil with a smooth flat roller, stacking the two materials, and rolling and laminating them at a rolling force of 8 kN and a rolling speed of 0.1 m / min to obtain a composite ultra-thin strip;
[0058] S5. Put the composite ultra-thin strip into an annealing furnace and perform post-rolling annealing treatment under argon protection. The post-rolling annealing treatment temperature is 850° C. and the holding time is 3 min. After the heat treatment is completed, the material is cooled to room temperature with the furnace to obtain a copper / 304 stainless steel composite ultra-thin strip.
[0059] Replacing the textured roll with a smooth flat roll does not achieve lamination.
[0060] Example 3 A grinding-free preparation process for a titanium / 304 stainless steel composite ultra-thin strip, the steps are as follows:
[0061] S1. Precisely cut a titanium foil with a thickness of 20 μm and a 304 stainless steel ultra-thin strip with a thickness of 20 μm as a composite metal substrate, and the specifications of the substrates are both 130 mm×15 mm;
[0062] S2, the cut titanium foil and 304 stainless steel ultra-thin strip are placed in an annealing furnace respectively, and annealed before rolling under argon protection, wherein the annealing temperature before rolling of 304 stainless steel is 950°C, the holding time is 5 minutes, and the annealing temperature before rolling of titanium foil is 600°C, the holding time is 10 minutes. After the annealing is completed, the material is cooled to room temperature with the furnace;
[0063] S3. Use dust-free paper to gently wipe the surface of the titanium foil and 304 stainless steel ultra-thin strip to be composited to remove possible oil stains and impurities;
[0064] S4, closely laminating the treated 304 stainless steel ultra-thin strip with a roughened roller with a roughness of 15 μm, laminating the titanium foil with a smooth flat roller, stacking the two materials, and rolling and laminating them at a rolling force of 10 kN and a rolling speed of 0.1 m / min to obtain a composite ultra-thin strip;
[0065] S5. Put the composite ultra-thin strip into an annealing furnace and perform post-rolling annealing treatment under argon protection. The post-rolling annealing treatment temperature is 650° C. and the holding time is 3 min. After the heat treatment is completed, the material is cooled to room temperature with the furnace to obtain a titanium / 304 stainless steel composite ultra-thin strip.
[0066] Replacing the textured roll with a smooth flat roll does not achieve lamination.
[0067] Example 4 A grinding-free preparation process for a titanium / 304 stainless steel composite ultra-thin strip, the steps are as follows:
[0068] S1. Precisely cut a titanium foil with a thickness of 20 μm and a 304 stainless steel ultra-thin strip with a thickness of 10 μm as a composite metal substrate, and the specifications of the substrates are both 130 mm×15 mm;
[0069] S2, the cut titanium foil and 304 stainless steel ultra-thin strip are placed in an annealing furnace respectively, and annealed before rolling under argon protection, wherein the annealing temperature before rolling of 304 stainless steel is 950°C, the holding time is 5 minutes, and the annealing temperature before rolling of titanium foil is 600°C, the holding time is 10 minutes. After the annealing is completed, the material is cooled to room temperature with the furnace;
[0070] S3. Use dust-free paper to gently wipe the surface of the titanium foil and 304 stainless steel ultra-thin strip to be composited to remove possible oil stains and impurities;
[0071] S4, closely laminating the treated 304 stainless steel ultra-thin strip with a roughened roller with a roughness of 10 μm, laminating the titanium foil with a smooth flat roller, stacking the two materials, and rolling and laminating them at a rolling force of 8 kN and a rolling speed of 0.1 m / min to obtain a composite ultra-thin strip;
[0072] S5. Put the composite ultra-thin strip into an annealing furnace and perform post-rolling annealing treatment under argon protection. The post-rolling annealing treatment temperature is 650° C. and the holding time is 3 min. After the heat treatment is completed, the material is cooled to room temperature with the furnace to obtain a titanium / 304 stainless steel composite ultra-thin strip.
[0073] Replacing the textured roll with a smooth flat roll does not achieve lamination.
[0074] Example 5 A grinding-free preparation process for a titanium / copper composite ultra-thin strip, the steps are as follows:
[0075] S1. Precisely cut a titanium foil with a thickness of 20 μm and a copper foil with a thickness of 20 μm as a composite metal substrate, wherein the specifications of the substrate are 130 mm×15 mm;
[0076] S2, placing the cut titanium foil and copper foil into an annealing furnace respectively, and performing pre-rolling annealing treatment under argon protection, wherein the pre-rolling annealing treatment temperature of the copper foil is 500°C, the holding time is 10 minutes, and the pre-rolling annealing treatment temperature of the titanium foil is 600°C, the holding time is 10 minutes, and after the annealing is completed, the material is cooled to room temperature with the furnace;
[0077] S3. Use dust-free paper to gently wipe the surfaces of the titanium foil and copper foil to be composited to remove possible oil stains and impurities;
[0078] S4, closely laminating the treated titanium foil with a roughened roller having a roughness of 15 μm, laminating the copper foil with a smooth flat roller, stacking the two materials, and rolling and laminating them at a rolling force of 7 kN and a rolling speed of 0.1 m / min to obtain a composite ultra-thin strip;
[0079] S5. Put the composite ultra-thin strip into an annealing furnace and perform post-rolling annealing treatment under argon protection. The post-rolling annealing treatment temperature is 650° C. and the holding time is 3 min. After the heat treatment is completed, the material is cooled to room temperature with the furnace to obtain a titanium / copper steel composite ultra-thin strip.
[0080] Replacing the textured roll with a smooth flat roll does not achieve lamination.
[0081] Example 6 A grinding-free preparation process for a titanium / copper composite ultra-thin strip, the steps are as follows:
[0082] S1. Precisely cut a titanium foil with a thickness of 10 μm and a copper foil with a thickness of 20 μm as a composite metal substrate, wherein the specifications of the substrate are both 130 mm×15 mm;
[0083] S2, placing the cut titanium foil and copper foil into an annealing furnace respectively, and performing pre-rolling annealing treatment under argon protection, wherein the pre-rolling annealing treatment temperature of the copper foil is 500°C, the holding time is 10 minutes, and the pre-rolling annealing treatment temperature of the titanium foil is 600°C, the holding time is 10 minutes, and after the annealing is completed, the material is cooled to room temperature with the furnace;
[0084] S3. Use dust-free paper to gently wipe the surfaces of the titanium foil and copper foil to be composited to remove possible oil stains and impurities;
[0085] S4, closely laminating the treated titanium foil with a roughened roller having a roughness of 10 μm, laminating the copper foil with a smooth flat roller, stacking the two materials, and rolling and laminating them at a rolling force of 7 kN and a rolling speed of 0.1 m / min to obtain a composite ultra-thin strip;
[0086] S5. Put the composite ultra-thin strip into an annealing furnace and perform post-rolling annealing treatment under argon protection. The post-rolling annealing treatment temperature is 650° C. and the holding time is 3 min. After the heat treatment is completed, the material is cooled to room temperature with the furnace to obtain a titanium / copper composite ultra-thin strip.
[0087] Replacing the textured roll with a smooth flat roll does not achieve lamination.
[0088] Test Example 1
[0089] The performance of the composite ultra-thin strips obtained in Examples 1-5 was tested, and the results are shown in Table 1.
[0090] Table 1 Test results of composite ultra-thin strip performance
[0091]
[0092] As can be seen from Table 1, the composite ultra-thin belt of the present invention has good electrical conductivity and thermal conductivity. The electrical conductivity of the steel-titanium composite ultra-thin belt is inferior to that of the copper-steel composite ultra-thin belt and the copper-titanium composite ultra-thin belt, but its performance in mechanical properties is relatively outstanding. The electrical conductivity of the steel-titanium composite ultra-thin belt is inferior to that of the copper-steel composite ultra-thin belt and the copper-titanium composite ultra-thin belt, and its performance in mechanical properties is relatively outstanding. The electrical conductivity and thermal conductivity of the copper-titanium composite ultra-thin belt are relatively outstanding, and its mechanical properties are inferior to the steel-titanium composite ultra-thin belt but better than the copper-steel composite ultra-thin belt. The electrical conductivity and thermal conductivity of the copper-titanium composite ultra-thin belt are relatively outstanding, and its mechanical properties are inferior to the steel-titanium composite ultra-thin belt but better than the copper-steel composite ultra-thin belt. It can be seen that the electrical conductivity of the composite ultra-thin belt decreases with the decrease of thickness, and the thermal conductivity decreases with the increase of thickness. The electrical conductivity of composite ultra-thin belts of different materials is ranked as copper-steel>copper-titanium>steel-titanium, and the thermal conductivity is ranked as copper-titanium>copper-steel>steel-titanium.
[0093] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A grinding-free preparation process for a double-layer metal composite ultra-thin strip, characterized in that: The following steps are involved: S1. Precisely cutting the metal thin strip to obtain the metal substrate; S2, annealing the metal substrate before rolling; S3, cleaning the metal substrate after annealing before rolling; S4, stacking the cleaned metal substrates and rolling them together with a textured roller and a conventional flat roller; S5. After rolling is completed, post-rolling annealing and cooling are performed to obtain a double-layer metal composite ultra-thin strip.
2. The preparation process according to claim 1, characterized in that: The extremely thin metal strip is any two of copper foil, titanium foil and alloy strip.
3. The preparation process according to claim 2, characterized in that: The alloy belt is a stainless steel belt.
4. The preparation process according to claim 1, characterized in that: The annealing temperature before rolling is preferably 500° C. to 950° C., and the holding time is preferably 5 to 10 minutes.
5. The preparation process according to claim 1, characterized in that: The pre-rolling annealing is performed in an inert gas atmosphere.
6. The preparation process according to claim 1, characterized in that: The textured roller is laminated to a metal substrate with high hardness, and the conventional flat roller is laminated to a metal substrate with low hardness.
7. The preparation process according to claim 1, characterized in that: The rolling force of the rolling is 7-12 kN, and the rolling speed is 0.1 m / min.
8. The preparation process according to claim 1, characterized in that: The post-rolling annealing temperature is preferably 650° C. to 850° C., and the holding time is 3 to 10 minutes.
9. The preparation process according to claim 1, characterized in that: The post-rolling annealing is performed in an inert gas atmosphere.
10. Application of a double-layer metal composite ultra-thin strip in the aerospace and electronics industries, characterized in that: The double-layer metal composite ultra-thin strip is prepared by the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for continuously rolling metal composite substrate by corrugated roll and a flat roll
CN108672494A
Transverse vibration rolling system for double-layer metal composite ultra-thin strip and preparation method
CN111389919A
Copper-aluminium bilayer structure composite thin belt and preparation method thereof
CN111618093A
Preparation method for aluminum alloy plate strip with roughened surface for anodic oxidation
CN112122383A
Preparation process of multilayer metal composite belt
CN113477712A